2013
DOI: 10.3402/ijch.v72i0.21142
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of invasive disease due toHaemophilus influenzaeserotype a in the Canadian North from 2000 to 2010

Abstract: IntroductionThe International Circumpolar Surveillance (ICS) project is a population-based surveillance network. Since 2000, Canada has participated in the ICS Invasive Bacterial Disease Working Group's surveillance of invasive disease due to Haemophilus influenzae (Hi).MethodsA standardized case report form containing demographic and clinical information was completed for all reported Hi cases in the study regions. Isolates were sent to a reference laboratory for confirmation and serotyping. Analysis was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 23 publications
(30 reference statements)
5
25
0
2
Order By: Relevance
“…These findings are consistent with previous Canadian and international circumpolar studies (3)(4)(5)(6)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings are consistent with previous Canadian and international circumpolar studies (3)(4)(5)(6)(21)(22)(23).…”
Section: Discussionsupporting
confidence: 83%
“…Some studies suggested that poor health, environmental and housing conditions of Indigenous children may be potential risk factors (28)(29)(30)(31). Hia has been a predominant serotype in Northern Canada since the beginning of ICS (5,22,32), whereas non-typaeble Hi and type f are more common in other circumpolar regions (32). This report also demonstrates the significant increasing trend of Hia.…”
Section: Discussionsupporting
confidence: 57%
“…Similar to Hib, Hia causes severe illness such as meningitis, sepsis and bacteremic pneumonia in young children under the age of five. Since northern Canada has a relatively high indigenous population and Hia, being similar to Hib including its epidemiology, has replaced Hib as a cause of significant burden of invasive diseases in the post-Hib vaccine era (17). This trend has also been observed in Alaska, U.S.A. (18).…”
Section: Invasive Haemophilus Influenzae Disease In Canadamentioning
confidence: 59%
“…Ces résultats sont cohérents avec les résultats des études circumpolaires canadiennes et internationales précédentes (3)(4)(5)(6)(21)(22)(23) …”
Section: Discussionunclassified